Introduction to Treaty of Waitangi Special Issue - Wilson, Bill (Victoria University of Wellington Law Review, 1995)
The Board of the New Zealand Institute of Advanced Legal Studies held a Conference on 9 and 10 February 1995 on the subject of "Treaty Claims: The Unfinished Business". This issue of the Victoria University of Wellington Law Review presents papers from this Conference. In introducing the issue, Wilson identifies four major themes emerging from the discussion. First, in considering Treaty of Waitangi issues, there is a tendency for Māori and non-Māori to talk past each other rather than to each other. Secondly, the "fiscal envelope" contained in the Crown's proposals is likely to be of very limited practical significance because all avenues for the resolution of Treaty claims will remain open, whatever the fate of the envelope. Thirdly, while the resolution of Treaty claims must be on an Iwi basis, full regard must be had to the position of all Māori in the application of the proceeds of settlements. Finally, New Zealand must consider new structures which recognise the position of Māori.